Dextranases from oral bacteria: inhibition of water-insoluble glucan production and adherence to smooth surfaces by Streptococcus mutans. - Schachtele, C F (1975)
The effect of dextranases (EC 3.2.1.11) from the oral isolates Actinomyces israelii and Bacteroides ochraceus on water-insoluble glucan production by the Streptococcus mutans dextransucrase (EC 2.4.1.5) and sucrose-dependent adherence to smooth glass surfaces by S. mutans was studied. Collection on membrane filters of water-insoluble polysaccharides synthesized from radioactive sucrose was used to demonstrate the marked sensitivity of insoluble glucan formation to the presence of dextranase. Concentrations of A. israelii dextranase as low as 0.002 U/ml inhibited insoluble glucan formation by 60%. Similar results were obtained the the B. ochraceus enzyme. An assay for sucrose-stimulated adherence of S. mutans to smooth surfaces involved attachment of radioactively labeled nongrowing cells to the bottom of glass scintillation vials. This facile and sensitive assay was utilized to demonstrate that sucrose-dependent adherence was affected by low levels of dextranase from either A. israelii or B. ochraceus. Enzyme at 0.005 U/ml reduced adherence of S. mutans by 80%. Treatment of S. mutans cells previously attached to glass with low concentrations of the dextranases resulted in removal of 50% to 60% of the bacteria. The results indicate that dextranase-producing oral bacteria may affect sucrose-dependent colonization of S. mutans on the tooth surface and offer a possible explanation for both the difficulties involved in implanting this bacterium into the human mouth and the limited intraoral transmission of S. mutans from one tooth surface to another.